New yellow-orange-red emitting phosphor Ca1-xSrx(SySe1-y):Eu2+with predicted properties for white light application - Nazarov, Mihail (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2006)
The highly efficient red-orange-yellow emitting phosphor (Ca1-xSrx)(S1-ySey):Eu2